2018
DOI: 10.1016/j.ijsu.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Can concurrent high-risk endometrial carcinoma occur with atypical endometrial hyperplasia?

Abstract: High-risk endometrial cancer can coexist with AEH. It should be remembered that despite preoperative and FS examinations, these high-risk tumors can be overlooked until final pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 22 publications
3
25
0
2
Order By: Relevance
“…In our case, the higher percentage of women undergoing HSC-res increased the diagnostic accuracy of AEH by decreasing EC instances. Recently, Erdem et al also showed an EC rate of 25.1% in 227 women with AEH confirming our results [20].…”
Section: Discussionsupporting
confidence: 92%
“…In our case, the higher percentage of women undergoing HSC-res increased the diagnostic accuracy of AEH by decreasing EC instances. Recently, Erdem et al also showed an EC rate of 25.1% in 227 women with AEH confirming our results [20].…”
Section: Discussionsupporting
confidence: 92%
“…This ratio has seen 10-59% in the literature [4,6,7]. Although this ratio is very wide, our rate is consistent with many studies in the literature [14][15][16][17]. However, the rate of our study is less than the results of some studies.…”
Section: Discussionsupporting
confidence: 89%
“…These tumors are often high-grade, have a poor prognosis, and not obviously associated with estrogen stimulation and the precursor lesion [11][12][13]. In many studies,The existence of atypia in endometrial hyperplasia has been shown as an independent risk factor for concurrent EC [13,4,[14][15][16][17]. It should be kept in mind that while most studies focus on atypical hyperplasia and other risk factors, there may be simultaneous endometrial canser with non-atypical endometrial hiperplasias.…”
Section: Evaluation Of Concurrent Endometrial Cancer In Patients Withmentioning
confidence: 99%
“…Therefore, this study recommended preparing frozen sections of specimens from preoperative sampling for all patients operated for atypical hyperplasia. Moreover, Erdem et al15 found that 25.1% of cases diagnosed as atypical hyperplasia using biopsies actually had coexisting Ca following excision, and 3% of them were high-risk cancers that had been overlooked during the examination of both biopsies and frozen sections.…”
Section: Discussionmentioning
confidence: 99%